2019
DOI: 10.1016/j.jid.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-11–Mediated Cell Death Contributes to the Pathogenesis of Imiquimod-Induced Psoriasis

Abstract: Data availability statement No datasets were generated or analyzed during this current study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Caspase-11 has been shown to play a role in the cleavage of GSDMD and development of psoriatic lesions in imiquimod-induced psoriasis in mice. 124 A previous study demonstrated that the caspase-11/4-GSDMD pathway was activated in the liver during alcoholic hepatitis. 125 In a mouse model of alcoholic hepatitis, a caspase-11 deficiency abolished the ductular reaction, hepatocellular death, and liver bacterial load, which implies that caspase-11 contributes to the pathogenesis of alcoholic liver disease.…”
Section: Inflammasome-related Diseasesmentioning
confidence: 98%
See 1 more Smart Citation
“…Caspase-11 has been shown to play a role in the cleavage of GSDMD and development of psoriatic lesions in imiquimod-induced psoriasis in mice. 124 A previous study demonstrated that the caspase-11/4-GSDMD pathway was activated in the liver during alcoholic hepatitis. 125 In a mouse model of alcoholic hepatitis, a caspase-11 deficiency abolished the ductular reaction, hepatocellular death, and liver bacterial load, which implies that caspase-11 contributes to the pathogenesis of alcoholic liver disease.…”
Section: Inflammasome-related Diseasesmentioning
confidence: 98%
“…Psoriasis is a chronic inflammatory skin disease that is characterized by scaling, erythema, and acanthosis with the infiltration of immune cells. Caspase‐11 has been shown to play a role in the cleavage of GSDMD and development of psoriatic lesions in imiquimod‐induced psoriasis in mice 124 . A previous study demonstrated that the caspase‐11/4–GSDMD pathway was activated in the liver during alcoholic hepatitis 125 .…”
Section: Physiological Implicationsmentioning
confidence: 99%
“…Despite the importance of caspase-4 and -5 activation in pathogen clearance, their inflammatory signalling is implicated in driving numerous non-infectious inflammatory pathologies ( Salskov-Iversen et al, 2011 ; Flood et al, 2015 ; Kajiwara et al, 2016 ; Kenealy et al, 2019 ; Zaslona et al, 2020a ; Zasłona et al, 2020b ). The exact circumstances leading to inappropriate activation of inflammatory caspases during sterile inflammation is unclear and suggests the existence of endogenous ligands.…”
Section: Lps-independent Activators Of Caspases-4 and -5mentioning
confidence: 99%
“…Dataset analysis showed a significant elevation of caspase-4/5, pro- IL-1β, and GSDMD in human psoriatic lesions. Besides, caspase-11 contributed to the pathogenesis of imiquimod-induced psoriasis in mice through the mediation of GSDMD activation and cell death ( 70 ). The process of GSDMD-dependent pyroptosis also took part in RA through the releasement of inflammatory mediators ( 71 ).…”
Section: Gsdmdmentioning
confidence: 99%